Nursery technique for mass propagation of Banana Musa acuminata cv. Berangan. - Ahmad Yusuf Mohd Kamil (2016)
This thesis presents an improved technique for mass propagation of banana planting material. The technique called corm nursery technique (Corm-Tech). Corm-Tech is divided into 2 parts, the pre-nursery stage and the polybag-nursery stage. Corm-Tech utilizes slices of mother corm obtained after harvest and corm from sword and water sucker. At the pre-nursery stage, the sliced corms were laid out on the bed of cocopeat, after that, the exposed surface was covered with Polyethylene Tarp (PE) to induce shoot and root growth. From the results, Corm-Tech produced significantly more seedlings than conventional nursery practice with respective seedling number of 116 and 42. Corm-Tech also produces higher quality banana planting material compared to the conventional method in terms of growth and development, which was significantly different at 0.05 significance level with the girth size of 7.22cm and height of 29.36cm. It was also found that sword sucker produced superior seedlings for both Corm-Tech and conventional method. For the different slices of mother corm, upper slices produced more seedlings compared to lower slices and whole corm with respective seedling number of 52, 23 and 35. Moreover, upper slices produced seedling with better quality with the girth size of 7.75cm and height of 33.00cm. The seedling growth and development were further improved through enhancement treatment. The seedlings physical criterion (parameters) was improved and the nursery period was shortened through enhancement treatment. There were two treatments were used which are shading and foliar fertilizer treatments. Under shading treatment, there were two level of treatments which were shaded (50.000lx) and unshaded (100.000lx). The enhancement study of shading treatment found that, seedlings under shade were taller than under direct sunlight with respective seedling height of 23.2cm and 17.8cm. Under foliar fertilizer treatment, the seedlings were treated with 5 different concentrations of foliar fertilizer which were Control (without fertilizer), 0.625g/l, 1.25g/l, 2.5g/l and 5g/l. At concentrations of 2.5g/l, it significantly improved the seedling growth with girth size of 8.13cm and height of 34.38cm. Overall, mass propagation of quality banana seedling was achieved by using this technique. This technique is a low-cost technology where the growers can establish the nursery in their own farm where it leads to the advantages of easy accessibility, affordability and readily available of planting materials to small scale growers to manage their farm. Apart from this, it can be modified to use for tissue culture plantlet nursery establishment in order to reduce the nursery propagation period from 3 months to 1 month. By doing so, mass propagation of banana seedling through tissue culture technique (during the nursery stage) can be produced within a shorter period and this will reduce cost of tissue culture seedlings for the growers.